2017
DOI: 10.1161/atvbaha.116.308728
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Impact of Smoking and Smoking Cessation on Inflammatory Markers of Cardiovascular Disease Risk

Abstract: Objectives To evaluate longitudinal changes in six inflammatory markers that predict cardiovascular disease events among smokers making a quit attempt and to characterize their cross-sectional associations between smoking and smoking heaviness. Approach and Results In a longitudinal cohort study of contemporary smokers (N=1652), we evaluated (i) independent associations of smoking heaviness markers (exhaled carbon monoxide, cigarettes/day, pack-years) with inflammatory markers (C-reactive protein [CRP], D-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 39 publications
6
59
0
Order By: Relevance
“…Our results are consistent with prior findings that show a relationship between cigarette smoking and vascular inflammation [ 9 11 , 13 , 38 , 39 ]. Smoking has been shown to modulate inflammation by activating the NF- K B pathway thereby inducing the transcription of genes involved in the innate immune response [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with prior findings that show a relationship between cigarette smoking and vascular inflammation [ 9 11 , 13 , 38 , 39 ]. Smoking has been shown to modulate inflammation by activating the NF- K B pathway thereby inducing the transcription of genes involved in the innate immune response [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, a more recent, albeit smaller study, found no significant difference (p ¼ 0.09) (Bazzano et al 2003). In another study, there was no reduction in FBG levels in subjects who refrained from smoking for 1 year (King et al 2017) One study found no significant difference between smokers who continued to smoke conventional cigarettes compared to those who switched to an RRP (p ¼ 0.88) (Nordskog et al 2015). It is important to note that many studies have shown that the functionality of FBG as an acute phase protein in response to inflammatory conditions is better reflected in changes in CRP than in corresponding changes of FBG levels (Al Rifai et al 2017).…”
Section: Fibrinogen (Fbg)mentioning
confidence: 83%
“…18,19 Furthermore, smoking has also been suggested to influence the levels of different inflammatory markers including white blood cells. 20 Therefore, in another sensitivity analysis, we further adjusted for smoking status. Information on smoking was gathered from different sources in the AMORIS cohort, including a number of cohort studies and the Swedish Medical Birth Register.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has a known inverse relationship with PD and has recently been suggested to be causally related to the risk of ALS . Furthermore, smoking has also been suggested to influence the levels of different inflammatory markers including white blood cells . Therefore, in another sensitivity analysis, we further adjusted for smoking status.…”
Section: Methodsmentioning
confidence: 99%